2005
DOI: 10.1158/0008-5472.can-04-3545
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Snail Induces Tumor Cell Invasion through Modulation of the Epithelial Cell Differentiation Program

Abstract: Abberant activation of the process of epithelial-mesenchymal transition in cancer cells is a late event in tumor progression.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
180
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(193 citation statements)
references
References 22 publications
8
180
0
3
Order By: Relevance
“…In fact, direct binding of SNAI1/SNAI2 to conserved E-box elements in the corresponding promoters has been reported for occludin, claudin-1 and claudin-7 (Ikenouchi et al, 2003;Martı´nez-Estrada et al, 2006). Interestingly, downregulation of claudin-4, the junctional adhesion molecule-1 (JAM-1/JAM-A) and Dlg3 has been detected in gene profiling studies of carcinoma cells, as well as in Madin-Darby canine kidney (MDCK) cells undergoing EMT after expression of SNAI1, SNAI2, E47 or other EMT regulators (De Craene et al, 2005b;Moreno-Bueno et al, 2006;Peinado et al, 2008). Because of the close relationship between tight junctions and the organization of epithelial cell polarity, these observations suggest that components of the core cell polarity complexes could also be direct targets of EMT transcriptional regulators.…”
Section: Regulation Of Cell Polarity Genes During Emtmentioning
confidence: 91%
See 1 more Smart Citation
“…In fact, direct binding of SNAI1/SNAI2 to conserved E-box elements in the corresponding promoters has been reported for occludin, claudin-1 and claudin-7 (Ikenouchi et al, 2003;Martı´nez-Estrada et al, 2006). Interestingly, downregulation of claudin-4, the junctional adhesion molecule-1 (JAM-1/JAM-A) and Dlg3 has been detected in gene profiling studies of carcinoma cells, as well as in Madin-Darby canine kidney (MDCK) cells undergoing EMT after expression of SNAI1, SNAI2, E47 or other EMT regulators (De Craene et al, 2005b;Moreno-Bueno et al, 2006;Peinado et al, 2008). Because of the close relationship between tight junctions and the organization of epithelial cell polarity, these observations suggest that components of the core cell polarity complexes could also be direct targets of EMT transcriptional regulators.…”
Section: Regulation Of Cell Polarity Genes During Emtmentioning
confidence: 91%
“…Apart from E-cadherin, other epithelial genes initially downregulated by Snail and ZEB factors are components of the tight junctions, including occludin and several members of the claudin family (Ikenouchi et al, 2003;Ohkubo and Ozawa, 2004;De Craene et al, 2005b;Vandewalle et al, 2005;Martı´nez-Estrada et al, 2006). In fact, direct binding of SNAI1/SNAI2 to conserved E-box elements in the corresponding promoters has been reported for occludin, claudin-1 and claudin-7 (Ikenouchi et al, 2003;Martı´nez-Estrada et al, 2006).…”
Section: Regulation Of Cell Polarity Genes During Emtmentioning
confidence: 99%
“…Cdx2, a transcription factor inducing intestinal metaplasia in the gastric epithelium, 31 has positively regulated the expression of claudin-4 during gastric carcinoma intestinal differentiation. 39,48 Snail and twist that have a central role in the epitheliummesenchymal transition (EMT), have been shown to repress claudin-4 expression in mouse epithelial cells, 49 colorectal cancer cells 50 and breast cancer cells. 51 In addition, tumorigenesis-associated TGF-b and Ras signaling pathways were reported to affect CLDN4 expression in pancreatic cancer cells.…”
Section: Bivalent Histone Modifications Are Associated With Cldn4 Repmentioning
confidence: 99%
“…This process is essential for gastrulation, neural crest formation, kidney development and so on (reviewed by Thiery, 2003). Several proteins have been identified that downregulate E-cadherin expression including SNAI1/SNAIL (Batlle et al, 2000;Cano et al, 2000), ZFHX1B/SIP1 (Comijn et al, 2001), SNAI2/SLUG (Hajra et al, 2002;De Craene et al, 2005), TWIST1 (Yang et al, 2004) and DeltaEF1 (Eger et al, 2005). Altered expression of these transcription factors seems to be also associated with an altered overexpression of transcriptional repressors of E-cadherin in tumour cells (Batlle et al, 2000;Cano et al, 2000;Comijn et al, 2001;Hajra et al, 2002;Yang et al, 2004;Eger et al, 2005).…”
mentioning
confidence: 99%